How Pre-School Aged Siblings Influence Toddlers' Language Development - Hnin Ze Hlaing; Hnin Ze Khine (Winaya Inspirasi Nusantara Foundation, 2026)
This study explores early first language development in toddlers, focusing on how children acquire semantic relations at the two-word stage. The purpose of the research is to examine this development through the lens of behaviorist theory and to investigate the influence of behavioral language input from family members, particularly mothers and siblings. The study involves four toddlers aged 24–28 months and compares two groups: children with no siblings and those with preschool-aged siblings. Data was collected over a three-month period through observation of the children’s utterances, with analysis focusing on Mean Length of Utterance (MLU) measured three times and the types of semantic relations produced. The results indicate that children exposed to richer behavioral language input, especially those with older siblings, tend to show greater development in MLU and a wider range of semantic relations. These findings suggest that interaction within the home environment plays a significant role in language development at the two-word stage. The study highlights the importance of providing consistent and meaningful language input to support early linguistic growth in young children.